Kemandirian Desa di Era UU No. 3 Tahun 2024: Tinjauan terhadap Kebijakan dan Praktik - Abdul Supardi (Community Engagement and Emergence Journal (CEEJ), 2024)
Law No. 3 of 2024 presents a significant opportunity for fostering village autonomy in Indonesia. The policies derived from this legislation, when executed effectively, can enhance the ability of villages to manage local assets and uplift community welfare. Nevertheless, the challenges encountered during this process should not be overlooked. Disparities in resources, reliance on governmental aid, and insufficient community engagement are among the hurdles that must be addressed. Recommendations for bolstering village autonomy encompass the enhancement of fundamental infrastructure in rural areas, improving community access to information and technology, and fostering active community engagement in the developmental planning process. Moreover, it is essential to reinforce continuous education and training initiatives to elevate community skills and knowledge in enterprise management. With these measures, it is anticipated that village self-sufficiency can be achieved, yielding positive ramifications for national development. With robust autonomy, villages are poised to become epicenters of economic advancement while also contributing to social and cultural equilibrium in Indonesia.